Care Navigation for Methamphetamine Use Disorder - Alia Al-Tayyib; Deborah J. Rinehart; Karina G. Duarte; Aiden Gilbert; Chris Newton; Ryan Loh; Emily Bacon; Scott A. Simpson (JAMA Network Open, 2026)
Importance Stimulant-involved deaths continue to increase in the US, and methamphetamine use remains a weighty public health concern. Treating methamphetamine use disorders is complicated. Contingency management has demonstrated the best effectiveness but is not widely implemented. Objective To examine the effectiveness of dedicated care navigation in linking patients to treatment. Design, Setting, and Participants This prospective randomized clinical trial was conducted at an integrated safety-net health system in Denver, Colorado, between April 10, 2023, and December 31, 2024. Eligible participants were 18 years or older who had a methamphetamine-related encounter in an acute care setting; those with involuntary treatment holds, substance treatment in past 90 days or actively seeking treatment, and inability to provide consent were excluded. Participants completed baseline, 30-day, and 90-day study visits. Intervention Dedicated care navigation, incorporating contingency management principles, with a focus on addressing health-related social needs. Main Outcomes and Measures Linkage to treatment within 30 and 90 days of enrollment defined as a composite measure of at least 1 of the following: electronic health record data indicating a visit at the health system’s substance treatment clinic, a behavioral health encounter at an outpatient clinic, temporary residential treatment, or self-reported treatment on the 30- and/or 90-day follow-up survey. Results Of 192 participants enrolled in the Beginning Early and Assertive Treatment for Methamphetamine Use trial, 156 (81.3%) were male, and the median age was 39 (IQR, 31-47) years. Most participants were unstably housed (163 [84.9%]), not currently employed (158 [82.3%]), and without regular access to a working phone (94 [49.0%]). Of the 96 participants randomized to the intervention, 60 (62.5%) engaged in 2 or more navigation sessions, 45 (46.9%) completed the 30-day study visit, and 47 (49.0%) completed the 90-day study visit compared with 44 (46.3%) and 37 (38.5%), respectively, of the 96 randomized to the control arm. No statistically significant differences in treatment linkage were observed at 30 days (24 participants [25.0%] in both arms; risk ratio, 1.00 [95% CI, 0.61-1.63]) or 90 days post enrollment, (32 [33.3%] in intervention vs 24 [25.0%] in control arms; risk ratio, 1.33 [95% CI, 0.85-2.09]). Conclusions and Relevance In this randomized clinical trial, integrating principles of contingency management into the intervention may have increased engagement with a dedicated care navigator but did not increase likelihood of linkage to treatment for methamphetamine use disorder. Trial Registration ClinicalTrials.gov Identifier: NCT06033365